SYNTHESIS AND DEPOSITION OF GRAPHENE THIN FILMS USING MODIFIED HUMMERS CHEMICAL EXFOLIATION METHOD - TRIMADYA PUTRA ( NIM :10510016) ; Pembimbing Dr. Veinardi Suendo, ARIA
Nowadays, transparent conductors are intensively used in many electronic devices for various applications such as touch screens and thin film displays. Graphene is a two dimensional (2D) carbon material with a honeycomb-like structure that has potential as a transparent conductor with high electrical and thermal conductivity, as well as good mechanical properties. This research has been conducted on the modification graphene synthesis using chemical exfoliation based on the method developed by Hummers. Modifications include the burning step of graphite samples at temperatures of 1000 ˚C to reduce the amorphous phase, as well as replacing the oxidizer on each stage of oxidation processes. The first modification is to burn of graphite by flame at 1000 ˚C, the second modification is replacing NaNO3 oxidant by Ammonium peroxodisulfate (APS), the third modification is replacing KMnO4 oxidant by APS, and the fourth is to replace H2O2 oxidant by APS. Graphite oxide obtained from synthesis steps above, subsequently sonicated at room temperature to obtain graphene oxide dispersions in water. All the modifications have been managed to turn graphite into graphene oxide. This is proven by the typical Raman peak of graphene oxide namely the G band with low intensity at ~1591 cm- 1 and the D band with higher intensity at ~1310 cm- 1. UV Ã‚Â– Vis absorption spectra of graphene oxide dispersions in water show the absorption band at ~230 nm corresponds to the π - π* transition of the C=C bonds and at ~300 nm corresponds to n - π* transition of the carbonyl functional group in graphene oxide. Modified graphene oxide was reduced into graphene using phenylhydrazine on metal surface. Raman spectra of the graphene samples give similar features to graphene oxide but with narrower peaks, which indicate an increase in their crystallinity.